EFFECT OF KAEMPFERIA GALANGA RHIZOME EXTRACT ON HAEMATOLOGICAL PARAMETERS IN STREPTOZOTOCIN INDUCED DIABETIC WISTAR RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Diabetes mellitus is a metabolic disorder that is characterized by elevated blood glucose level, altered lipids, carbohydrates and protein metabolism. The present investigation was undertaken to determine the hypoglycemic potential of hydroethanolic extract of Kaempferia galanga rhizome and to assess haematological profile in diabetic rats. Adult male albino rats of Wistar strain were induced with diabetes by intraperitoneal injection of streptozotocin (STZ) (60 mg/kg body weight). Changes in haematological profile reported by STZ induced diabetic rats were found to be restored to normal condition upon administration of K. galanga extract in treated groups indicating hematoprotective effect of the extract. Diabetic rats exhibited increased level of serum glucose and reduced body weight compared to normal control rats. The K. galanga rhizome extract treated animals exhibited significant increase in body weight and reduced level of blood glucose thereby restoring to near normal levels. The present findings indicate that K. galanga rhizome can be considered for treating diabetes induced complications.